Drivers and Barriers in Biotechnologies Incorporating Wild Fauna into the Agri-Food Transition - Imio, Juan Carlos (2025)
The civilizational urgency to transition towards a sustainable agri-food system is promoting the development of agricultural methods and technologies that replace external chemical-based energy inputs. This research identifies the main drivers and perceived barriers among stakeholders regarding BATsignal, a biotechnological package that integrates bat ecosystem services into the operational framework of the agri-food system. The study employs the theoretical framework of socio-technical transitions to sustainability, using the Multi-Level Perspective (MLP) to address the complexity of this radical agricultural innovation. The research follows a qualitative case study design with a sample of 75 participants whose perceptions and experiences were gathered through semi-structured interviews and focus groups. The results revealed that the majority of stakeholders (farm owners, workers, professionals, agricultural scientists, and civil society members) support the incorporation of BATsignal into crop production. This acceptance is based on the multiple socio-cultural, economic, environmental, and health benefits perceived by the interviewees regarding the substitution of certain agrochemical inputs with bat-provided ecosystem services. However, the global media association of bats with the initial outbreak of the COVID-19 pandemic poses a challenge to the advancement of BATsignal from the socio-technical landscape.Finally, we argue that sustainable innovations that capitalize on the biological activity of wild-classified animals have opportunities within the agri-food transition, provided they detach from the practices and expectations of the dominant agro-industrial socio-technical regime.